2022
DOI: 10.1002/cplu.202200045
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Photovoltaic Performance and Thermal Stability of Organic Solar Cells via an Insulating Fluoropolymer Additive

Abstract: The use of processing additives is one of the most widely used approaches to optimizing the bulk heterojunction (BHJ) morphology for boosting the photovoltaic performance of organic solar cells (OSCs). Recently, insulating polymer-based additives have drawn great attention owing to the merits of good morphology-directing abilities, simple post treatments, rich functionality and enhanced device stabilities. In this contribution, a known fluoropolymer poly-p-trifluoromethylstyrene (PTFS) is selected as a solid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…In the past decades, various solvent additives have been developed to understand the complex mechanisms in the active layer. [21][22][23] Among them, it is noteworthy that the performance can be improved to uniform morphology features by introducing polymer additives, such as polydimethylsiloxane and styrene-butadienestyrene. [24][25][26][27] In addition, some studies reported that incorporating two different additives can reach high quality films with high performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, various solvent additives have been developed to understand the complex mechanisms in the active layer. [21][22][23] Among them, it is noteworthy that the performance can be improved to uniform morphology features by introducing polymer additives, such as polydimethylsiloxane and styrene-butadienestyrene. [24][25][26][27] In addition, some studies reported that incorporating two different additives can reach high quality films with high performance.…”
Section: Introductionmentioning
confidence: 99%